A 480 kW/liter direct injection jet ignition rotary valve super-turbocharged positive ignition methanol engine. (October 2020) - Boretti, Alberto
Abstract: The potentials of direct injection (DI) and jet ignition (JI), assisted turbocharging, and rotary valves to deliver high efficiency, high power density positive ignition (PI) internal combustion engines (ICEs) is here investigated. DI JI and assisted turbocharging has demonstrated to permit ICEs able to deliver peak efficiency above 50% and power density of 340 kW/liter at the 15, 000 rpm revolution limiter working overall λ = 1.45 with gasoline. The further improvement in power density that may be obtained by replacing poppet valves with rotary valves, while also using mechanical, rather than electric, assisted turbocharging, are here numerically investigated A numerical rotary valve ICE, that is adopting super-turbocharging is developed. Results of simulations show the opportunity, working overall λ = 1.45 with methanol, power densities of 480 kW/liter, while also delivering an about constant torque, and a consequently nearly linear power curve, over an extremely wide range of speeds, up to 24, 000 rpm. With gasoline, the power density is 450 kW/liter. The proposed engine design could be used to revive IndyCar racing, with methanol, for improved performance and technical appeal, or in military unmanned aerial vehicles (UAV) with gasoline, for enhanced range, altitude, payload, and maneuverability.